PREVALENCE AND RISK FACTORS OF TRICHOMONAS VAGINALIS INFECTION AMONG PREGNANT WOMEN RECEIVING ANTENATAL CARE IN ABEOKUTA, NIGERIA. - ETUKETU, Ivie Maureen; Mogaji, Hammed; Alabi, Oladimeji Micheal; Adeniran, Adebiyi Abdulhakeem; Oluwole, Akinola Stephen; Ekpo, Uwem Friday (African Journal of Infectious Diseases (AJID), 2015)
Background: Trichomoniasis is the most prevalent treatable sexually transmitted disease in the world. This study investigated the prevalence oftrichomoniasis and associated risk factors among pregnant women attending ante-natal sessions in a tertiary health care facility in Abeokuta.Materials and Methods: High Vaginal Swabs (HVS) were collected and analyzed microscopically from 300 randomly selected ante-natal attendees.Questionnaires were concurrently administered to investigate associated risk factors about infection. Descriptive analysis was employed using SPSS(IBM, Amonk, NY, USA) version 20.0 and associations were ascertained using Pearson chi square. Significance level was set at p≤ 0.05Results: An overall prevalence of 10.3% was recorded. Age group 40-44(14.8%) had the highest infection, while lowest infection was recordedamong age group 25-29(9%). Majority of the infected patients were married 26(11%) and in their second trimester stage of pregnancy 11(11.1%).Type of toilet used and shared usage of toiletries show significant relationship with infections among patients with (P=0.024) and (P=0.000)respectively. Occupational related prevalence showed that traders were the most infected 12(18.5%).Conclusion: Our findings present higher prevalence of Trichomonas vaginalis among older women of reproductive age. Poor hygiene practices andknowledge about infection are major risk factors predisposing patients to infection. However, measures geared towards promoting preventionmechanism/s through safe hygiene practices should be emphasized through public enlightenment programs. Inclusion of Trichomonas vaginalisclinical testing during antenatal care services will also assist prompt diagnosis, management and control of infection.